Excitatory synchronization of rat hippocampal interneurons during network activation in vitro - Pendeliuk, Viktoria S.; Melnick, Igor V. (Frontiers in Cellular Neuroscience, 2023)
Introduction Hippocampal interneurons (INs) are known to synchronize their electrical activity via mechanisms, which are poorly defined due to immense complexity of neural tissue but seem to depend on local cell interactions and intensity of network activity. Methods Here, synchronization of INs was studied using paired patch-clamp recordings in a simplified culture model with intact glutamate transmission. The level of network activity was moderately elevated by field electric stimulation, which is probably an analogue of afferent processing in situ. Results Even in baseline conditions, ∼45% of spontaneous inhibitory postsynaptic currents (sIPSCs) resulting from firing of individual presynaptic INs coincided between cells within ±1 ms due to simple divergence of inhibitory axons. Brief network activation induced an appearance of ‘hypersynchronous’ (∼80%) population sIPSCs occurring in response to coherent discharges of several INs with jitter ±4 ms. Notably, population sIPSCs were preceded by transient inward currents (TICs). Those were excitatory events capable to synchronize firing of INs, in this respect being reminiscent of so-called fast prepotentials observed in studies on pyramidal neurons. TICs also had network properties consisting of heterogeneous components: glutamate currents, local axonal and dendritic spikelets, and coupling electrotonic currents likely via gap junctions; putative excitatory action of synaptic gamma-aminobutyric acid (GABA) was not involved. The appearance of population excitatory-inhibitory sequences could be initiated and reproduced by firing of a single excitatory cell reciprocally connected with one IN. Discussion Our data demonstrate that synchronization of INs is initiated and dominated by glutamatergic mechanisms, which recruit, in a whole-sale manner, into supporting action other excitatory means existing in a given neural system.